The Phenomenon of Gadget Dependence in Learning in the Digital Era for Students - Rasulun Iman (MANDAILING GLOBAL EDUKASIA, 2025)
The development of digital technology has driven a significant transformation in the learning system in higher education. Gadgets, especially smartphones, have become the primary device supporting learning in the digital era. However, the high intensity of gadget use among students has also given rise to a phenomenon of dependency that has the potential to impact the quality of the learning process and outcomes. This study aims to examine the phenomenon of gadget dependency in learning in the digital era among students based on the results of previous research. The research method used is a qualitative approach with a library research type. Data were obtained from various scientific literature sources in the form of national and international journal articles relevant to the topic of gadget dependency and student learning. Data collection techniques were carried out through systematic literature searches, while data analysis used content analysis to identify and synthesize research findings. The results of the study indicate that gadget dependency among students impacts various aspects of learning, including decreased concentration, learning motivation, academic productivity, and the quality of social interactions. In addition, gadget dependency is influenced by low student self-control, less interactive learning designs, and a lack of digital literacy oriented towards the wise use of technology. Therefore, collaborative efforts are needed from universities, lecturers, and students to manage gadget use proportionally and productively. This research is expected to provide theoretical and practical contributions in the development of more effective and sustainable digital learning in higher education.